WISC-III: Instrumento para Confirmação de Altas Habilidades/Superdotação - Mendonça, Lurian Dionizio; Rodrigues, Olga Maria Piazentin Rolim; Capellini, Vera Lucia Messias Fialho (Conselho Federal de Psicologia, 2018)
Abstract The identification of students with giftedness is a complex and necessary process. In a state school located in a city of the State of São Paulo, 326 pupils who have attended to the early years of elementary school were evaluated in order to identify giftedness. Raven's Progressive Matrices test, the School Achievement Test and teacher's indication through an evaluation protocol were used. Seventy-four 6-11 years-old students presented giftedness indicators in two instruments at least. This study intended to confirm the high intellectual development of those pupils using the WISC-III. In order to confirm giftedness, the chosen criterion was to consider at least two indicators of the four instruments used: presenting a percentile of 90 or higher in Raven's test; obtaining at least two higher results in School Achievement Test subtests; being pointed by the teacher or achieving a result of 130 or higher in any subgroups (Verbal IQ, Execution IQ and Total IQ) on WISC-III. Eleven students were confirmed by these criteria. Fourteen students who reached at least one higher IQ on WISC-III were identified as well. The WISC-III results were considered suitable to confirm the identification of students with giftedness and, also, pointed a group of pupils who showed higher results, potentially with giftedness, and were benefited from specific services. Considering the age of the participants, it is suggested that WISC-III could be used to track their intellectual development with instruments which could evaluate their interests and skills.

Resumen La identificación de alumnos con altas habilidades/superdotación (AH/SD) es un proceso complejo y necesario. En una escuela estatal de una ciudad del interior del Estado de São Paulo, los 326 alumnos que frecuentaban los primeros años de la enseñanza primaria participaron en una selección para identificación de AH/SD. Se utilizó la prueba de las Matrices Progresivas de Raven, la Prueba de Desempeño Escolar y la indicación del profesor, a través de un protocolo de evaluación. 74 alumnos, de seis a 11 años de edad, presentaron indicadores de AH/SD en al menos dos de los instrumentos. El presente estudio pretendió confirmar el alto desempeño intelectual de ellos utilizando el WISC-III. Para confirmar las AH/SD, se adoptó el criterio de al menos dos indicadores, de los cuatro instrumentos aplicados: presentar un percentil de 90 o más en el Raven; tener por lo menos dos resultados superiores en las subpruebas de la Prueba de Desempeño Escolar; ser indicado por el profesor o presentar un CI de 130 o más en cualquiera de los subgrupos (CI Verbal, CI de Ejecución y CI Total) en el WISC-III. Se han confirmados 11 alumnos utilizando los criterios definidos. También se han identificados 14 alumnos que obtienen al menos un CI superior WISC-III. Los resultados apuntaron que el WISC-III se mostró adecuado para confirmar la identificación de alumnos con AH/SD y, también, apuntar un grupo de alumnos que presentaron resultados superiores, potencialmente con AH/SD, que se beneficiaría de servicios específicos. Considerando la edad de los participantes, se sugiere que el WISC-III se utiliza para supervisar sistemáticamente su rendimiento intelectual junto con instrumentos que evalúen sus intereses y habilidades.

Resumo A identificação de alunos com altas habilidades/superdotação (AH/SD) é um processo complexo e necessário. Em uma escola estadual de uma cidade do interior do estado de São Paulo, os 326 alunos que frequentavam os primeiros anos do ensino fundamental participaram de uma triagem para identificação de AH/SD. Utilizaram-se o teste das Matrizes Progressivas de Raven, o Teste de Desempenho Escolar (TDE) e a indicação do professor, via um protocolo de avaliação. Setenta e quatro alunos, de seis a 11 anos de idade, apresentaram indicadores de AH/SD em pelo menos dois dos instrumentos. O presente estudo pretendeu confirmar o alto desempenho intelectual deles utilizando o WISC-III. Para confirmar as AH/SD, adotou-se o critério de pelo menos dois indicadores, dos quatro instrumentos aplicados: apresentar um percentil de 90 ou mais no Raven; ter pelo menos dois resultados superiores nos subtestes do TDE; ser indicado pelo professor ou apresentar um QI de 130 ou mais em qualquer um dos subgrupos (QI Verbal, QI de Execução e QI Total) no WISC-III. Foram confirmados 11 alunos utilizando os critérios definidos. Também foram identificados 14 alunos que obtiverem pelo menos um QI superior no WISC-III. Os resultados apontaram que o WISC-III se mostrou adequado para confirmar a identificação de alunos com AH/SD e, também, apontar um grupo de alunos que apresentaram resultados superiores, potencialmente com AH/SD, que se beneficiariam de serviços específicos. Considerando a idade dos participantes, sugerese que o WISC-III seja utilizado para monitorar sistematicamente o seu desempenho intelectual juntamente com instrumentos que avaliem seus interesses e habilidades.
WISC-III: Instrument for Confirmation of Giftedness
WISC-III: Instrumento para la Confirmación de Altas Habilidades/Superdotación
Keywords: Psychological Testes; WISC-III; Special Education; Testes Psicológicos; WISC-III; Educação Especial